Profile Volatilome for Halal Authentication of Beef and Pork Corned Beef Using GC-MS - Nur Rahmawati, Anandhita Putri; Vevi Maritha; Weka Shidha Bhagawan; Puri Ratra Kartini; Desi Kusumawati; Avip Kurniawan (Strada Journal of Pharmacy, 2026)
The volatilomic approach to beef and pork corned beef is a method that can be used to provide an overview of the volatile compound profile and has high sensitivity and has been successfully used for halal authentication. The purpose of this study was to authenticate the halal status of beef and pork corned beef using the Gas Chromatography–Mass Spectrometry method. The research method used was a laboratory experimental study with a volatilomic approach using a combination of GC-MS and chemometric methods. The results showed that there were 242 volatile compounds in beef corned beef and 15 volatile compounds in pork corned beef. PCA analysis showed that the volatile compound profiles of beef corned beef and pork corned beef were different. Cluster analysis using dendrograms can classify information and identify patterns of volatile compound profiles in beef corned beef and pork corned beef that are well clustered. PLS-DA analysis results show that there are several volatile compounds that play a significant role in distinguishing between beef corned beef and pork corned beef. The compounds with the highest VIP (Variable Importance in Projection) values were hexadecanoic acid and pentadecanoic acid, which showed a dominant role in separating the two types of corned beef. A high VIP value (>1) indicates that the compound has a large contribution to the model.